Hermite - Hadamard type inequalities for (m; h1; h2)-convex stochastic processes using Katugampola fractional integral. - Hernández H, Jorge Eliecer (Revista MATUA, 2019)
In this article some inequalities of the Hermite-Hadamard type are presented for (m; h1; h2)-convex stochastic processes using the fractional integral of Katugampola, and from these results specific cases are deduced for other stochastic processes with generalized convexity properties using the Riemann-Liouville fractional integral and the Riemann integral .